Training and education practice in the Europe, Middle East and Africa, Latin America and Asia Oceania chapters, IFCN; an international survey - Jonathan Cole (Clinical Neurophysiology Practice, 2022)
This paper presents results from the first survey of training and education undertaken by the Europe-Middle East-Africa (EMEAC), the Latin America (LAC) and the Asia-Oceania (AOC) Chapters of the International Federation of Clinical Neurophysiology (IFCN). The survey was conducted initially by the EMEAC in 2012 and updated in 2016, 2019, and 2020. It had the following categories: status of specialty and training in member country (21 questions), competency and accreditation (12 questions), practice and concerns (23 questions). An abbreviated version of the survey was conducted by the LAC and AOC in 2018–2019.Clinical neurophysiology (CN) was a single specialty in a minority of member societies’ countries: 8/33 EMEAC, 2/12 AOC and 2/10 LAC. In others it was usually a subspecialty of neurology. Training periods in CN were split fairly evenly between 1, 2, 3, 4 and 5 years in EMEAC, while neurology takes 4 to 5 years. In the AOC, neurology training was for 3 to 4 years and CN for up to 2 years. In LAC a majority of countries trained for 2 to 3 years in both neurology and CN. An exit exam was performed in 16/30 EMEAC respondents, 8/12 in the AOC and 3/10 in the LAC.Competence was considered to require a wide range of numbers of tests performed under supervision, from <250 to >750 in EMEAC and AOC, with the EMEAC tending to require more. The main concerns were in recruitment and workload in EMEAC, training in AOC and the need for more recognition of the specialty in some countries within the LAC.This survey, the first across the three chapters, revealed considerable differences in training durations and numbers of tests performed for competence between national societies.